Development of general hydrodynamic modelling method for whiplash nerve injury: Using high-fidelity data from the ViVA+ human body model - Al-Debis, Hussein; Mahmoud, Aran (My University, 2022)
Vehicle collisions are an issue in the automotive industry, and one of the most common injury in vehicle collisions are whiplash injuries. The reason for the rise of such injury is caused by the occupant’s torso being accelerated along the collision direction while the unsupported head lags. Some usual sections in the human body which can be affected by a whiplash motion are spinal ligaments, dorsal root ganglion, and invertebral discs in the neck. In addition, there are studies that has recorded pressure transients in the spinal canal when necks are exposed of whiplash motions. These pressure transients explain some symptoms that are associated with whiplash injuries. This thesis aimed to develop an existing Matlab-Simulink program that computes pressure transients in the human spinal canal for all directions of neck motions. The current program was only customized for rear-end collisions, taking sagittal neck motion into account. Furthermore, the input in the program was customized to calculate volume changes in the spinal canal modelled with vertebral angular displacement, whereas the modifications done for this study was based on volume changes from human body model simulations. To obtain the volume changes for each vertebra, a human body model was used called ViVA+. With this approach, the purpose was to get similar results of volume change as the old program did with angular displacement for the sagittal direction. To perform modifications in the program and obtain the desired results, it was divided into different steps. Firstly, modeling in ViVA+ was completed, which was also based on computational settings with crash pulses. The modeling was created in different segments for the vertebras and in sections between each vertebra. Once the modeling was concluded, the desired volume could be achieved, which was put into the MATLAB program. Further, the MATLAB program had to be modified in such a way that it was possible to compute with different types of collisions and directions. For rear-end collisions, something that was noticed was that the airbags had an effect on the motion of the neck. With simulations completed, with and without airbags, it could be concluded that the one with airbags did not reach full extension. However, the amplitude of the pressure obtained was similar to the program’s old version. With the airbags capturing the volume of the segments in a three-dimensional way, it was possible to do the same for other directions, such as lateral motion. One issue regarding the rear-end collisions for not reaching full extension was that the implementation of airbags or its properties had an impact on the stiffness of the HBM. As the aim was to develop the program so that it was possible to calculate the pressure build-up for different directions, it could be concluded that the new modifications were successful, as it was possible to implement on side-collisions.
Keywords: vehicle collision; whiplash motion; pressure transients; spinal canal; angular displacement; ViVA+; airbags; human body model